1970
DOI: 10.1254/jjp.20.294
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Beta-Adrenergic Blocking Effect of Dci, Methoxamine, Propranolol, Mj 1999, H 56/28, Lb 46 and I.C.I. 50 172 on the Chronotropic Response to Isoprenaline

Abstract: In 1958, Powell and Slater (1) first described that DCI had beta-adrenergic blocking activity even though it included beta-adrenergic stimulations. Such property was found also in methoxamine besides its alpha-adrenergic stimulant activity (2, 3). In the follow ing decade, many beta-adrenergic blocking agents have been synthesized successively (4-8) and one of them, propranolol was first introduced in the clinical medicine. Since Ahlquist classified alpha and beta-adrenergic receptors, it has been well establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1971
1971
1975
1975

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The magnitude of the rise elicited by these i3-blocking agents and the minimum doses of these agents required to cause the pressor action appeared to be related to their E3-blocking activities in the heart such as was also reported by several investigators (24)(25)(26)(27). Therefore, the magnitude of the rise and the minimum dose of these agents could be used to compare the relative ( blocking activity of these agents.…”
Section: Discussionsupporting
confidence: 54%
“…The magnitude of the rise elicited by these i3-blocking agents and the minimum doses of these agents required to cause the pressor action appeared to be related to their E3-blocking activities in the heart such as was also reported by several investigators (24)(25)(26)(27). Therefore, the magnitude of the rise and the minimum dose of these agents could be used to compare the relative ( blocking activity of these agents.…”
Section: Discussionsupporting
confidence: 54%
“…Thus we conclude that OPC-1085 has a sympathomime tic action which is well known with alprenolol (18,19), Ko 1366 (10) and dichloroisopro terenol (20). Hashimoto et al (21) and Ohkuda et al (22) have observed that an intra arterial injection of a smaller dose of dichloroisoproterenol, pindolol, alprenolol or pra ctolol produced a positive chronotropic response in the in situ sino-atrial node prepara tion which is the same as was seen with Kb 1366, pindolol or practolol in the isolated blo od-perfused one (23). OPC-1085 induced a more prominent sympathomimetic effect with cumulative administration of increasing doses than did pindolol.…”
Section: Resultsmentioning
confidence: 76%